Perancangan Perabot Restoran Cepat Saji Dengan Material Stainless Steel - Kelvin Hamdany (Intra, 2017)
Now, the speed factor becomes dominant so it is considered an indicator for success. As a result, the value of time becomes so valuable that the concept of dining is no longer a necessity but merely an obligation. This makes every fast food restaurant a place to eat that continues to be visited by the community, because the speed of serving food can save more time needed to work. The formulation of the problem in this design is the type of element that should be considered in the design of quick service restaurant furniture with stainless steel material to support the acceleration of consumer replacement and furniture design models that can accelerate consumer reimbursement with stainless steel materials at quick service restaurants. The design process used the design thinking method with the following stages: understand, ideate, prototype, and implementation. The results of this design resulted in elements to be considered in the design of furniture for quick service restaurants with stainless steel, where stainless steel is well-known for its hardness, strength, cool and aesthetic look.  Models that can accelerate the The change of consumers by using stainless steel material for quick service restaurants should pay attention to the Standard dimension variation that already exist. The results of this design have been published through social media and personal web, this furniture will be used for quick service restaurants furniture.